2005
DOI: 10.1124/jpet.105.094979
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the mRNA, Protein, and Functional Expression of Organic Anion Transporter (Oat) 1, Oat3, and Organic Cation Transporter (Oct) 2 in Rabbit Renal Proximal Tubules

Abstract: Sex differences in transport of the organic anion (OA) substrate p-aminohippurate (PAH) and the organic cation (OC) substrate tetraethylammonium (TEA) have been recognized for some time. In the rat kidney, androgens up-regulate and estrogens down-regulate PAH and TEA transport, which correlate with similar changes in mRNA and protein expression for the renal basolateral membrane transporters organic anion transporter (Oat) 1 and organic cation transporter (Oct) 2. However, these sex differences are not readily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 30 publications
6
41
2
Order By: Relevance
“…These findings are in agreement with the previously published data on female-dominant expression of mOat3 mRNA and male-dominant expression of mOat1 mRNA and protein in mouse kidneys (9,15,18,39). Our experiments in castrated male mice clearly showed that the expression level of both transporters is dependent on androgens but in opposite directions; castration markedly upregulated the expression of mOat3 protein, suggesting an inhibitory effect of androgens on its expression, whereas the expression of mOat1 protein was downregulated by castration, suggesting a stimulatory effect of androgens on its expression.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These findings are in agreement with the previously published data on female-dominant expression of mOat3 mRNA and male-dominant expression of mOat1 mRNA and protein in mouse kidneys (9,15,18,39). Our experiments in castrated male mice clearly showed that the expression level of both transporters is dependent on androgens but in opposite directions; castration markedly upregulated the expression of mOat3 protein, suggesting an inhibitory effect of androgens on its expression, whereas the expression of mOat1 protein was downregulated by castration, suggesting a stimulatory effect of androgens on its expression.…”
Section: Discussionsupporting
confidence: 83%
“…7, C and D). These protein data are thus in agreement with the previously reported female-dominant expression of mOat3 mRNA (9,15,39).…”
Section: Characterization Of Roat3-ab By Fluorescence Immunocytochemisupporting
confidence: 82%
See 2 more Smart Citations
“…In addition to the organic cation system, renal tubule cells also display a comparable system for organic anions (20,21). Active transport of organic anions is an essential renal function, and organic anion transporters in the proximal tubule are responsible for transport of p-aminohippurate and hippuran analogs (22,23).…”
Section: Biodistribution and Dosimetrymentioning
confidence: 99%